2020
DOI: 10.1002/ppul.25055
|View full text |Cite
|
Sign up to set email alerts
|

Overview of gene therapy in spinal muscular atrophy and Duchenne muscular dystrophy

Abstract: Both 5q‐linked spinal muscular atrophy (SMA) and Duchenne muscular dystrophy (DMD) are fatal monogenic neuromuscular disorders caused by loss‐of‐function mutations. SMA is an autosomal recessive disorder affecting motor neurons that is typically caused by homozygous whole‐gene deletions of SMN1. DMD is an X‐linked recessive muscle disease most often due to exon deletions, but also duplications and smaller sized variants within the DMD gene. Gene replacement therapy offers the opportunity to correct the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 102 publications
0
30
0
Order By: Relevance
“…Still, only 14% of RNase-H-based ASOs and 20–40% of other ASO subclasses were tested in minipigs for non-rodent toxicity studies. ASOs are also of interest for pediatric indications, including neuromuscular diseases [ 34 , 35 , 36 ], such as spinal muscular atrophy [ 37 ] and Duchenne muscular dystrophy [ 38 ], which have already been treated successfully [ 6 ]. Moreover, ASOs are also being explored for the treatment of several other diseases in children such as retinopathy of prematurity [ 39 ], leukodystrophies [ 40 ], and inherited lung diseases [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, only 14% of RNase-H-based ASOs and 20–40% of other ASO subclasses were tested in minipigs for non-rodent toxicity studies. ASOs are also of interest for pediatric indications, including neuromuscular diseases [ 34 , 35 , 36 ], such as spinal muscular atrophy [ 37 ] and Duchenne muscular dystrophy [ 38 ], which have already been treated successfully [ 6 ]. Moreover, ASOs are also being explored for the treatment of several other diseases in children such as retinopathy of prematurity [ 39 ], leukodystrophies [ 40 ], and inherited lung diseases [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation of ex vivo edited stem cells has the potential to generate new healthy myofibers, while in vivo gene therapy, although most effective before extensive loss of muscle mass, has demonstrated the most dramatic and widespread effects in animal models (6). Multiple in vivo gene therapy human clinical trials are currently underway (14). In vivo CRISPR-Cas9mediated exon skipping, to ultimately yield truncated yet functional dystrophin, ameliorated pathology in both mouse and canine models of Duchenne muscular dystrophy (DMD) (12,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Several other promising gene therapies for hemophilia, Duchenne's muscular dystrophy (DMD), immunodeficiency, and Pompe disease are also progressing through clinical trials. [6][7][8][9] All of these therapies have demonstrated that gene delivery can be a lifesaving treatment for patients where other treatment mechanisms have failed. 4 However, several issues have arisen in regards to LV and AAV vehicles, including high treatment costs (e.g., $2M for Zolgensma®), safety concerns, and relatively low transduction efficiencies in some patients.…”
Section: Introductionmentioning
confidence: 99%